DEVELOPMENT OF TEST RIG FOR QUADROTOR FLIGHT TESTING INSIDE WIND TUNNEL USING MOTION CAPTURE SYSTEM - Muhammmad Zufar Jurij (Tesis, 2021)
This thesis present an experimental setup for the development and testing of quadrotor flight in an open jet wind tunnel with turbulence flow.